Markov chain application to the dynamics of the pelagic fishery along the Kerala coast, India - Srinath, M (Indian Journal of Fisheries, 2011)
The changing pattern of the composition of the pelagic fish assemblage inKerala in the context of the introduction of the ring-seine gear has beenmodelled with the help of Markov chain model. The transition probabilitiesof the species dominance with respect to four dominant groups, namely,oilsardine, muckerel, whitebait and carangids before and after the introductionof the ring-seine have been estimated. The long term transition probabilitieshave also been computed with a view to predicting the status of the dominanceof the major pelagic groups